Effect Of Tax Justice, Tax System, Technology And Information, And Discrimination Of Personal Perspection Of Personal Tax Mandatory About Tax Ethics - Akbar Yoga Karunia Ikhsan Sudiro; Icuk Rangga Bawono; Rasyid Mei Mustofa (Universitas Serang Raya, 2021)
The purpose of this study is to determine the effect of tax justice, taxation systems, information technology, and discrimination against taxpayers' assessment of tax evasion. The population is limited to WP registered at KPP Pratama Kebumen. The sampling method uses the convenience sampling method and the minimum number of samples taken is 100 respondents based on the Slovin calculation. The data source comes from primary and secondary data. Retrieval of data derived from questionnaires is then processed with multiple linear regression assisted with SPSS version 25. The results state that (1) tax justice has a negative effect on WP's perception of tax evasion, (2) the taxation system has a negative influence with WP's perception of embezzlement tax, (3) technology and information have a negative effect on WP's perception of tax evasion, and (4) discrimination has a positive effect on WP's perception of tax evasion.